Analisis Determinan Produktivitas Tenaga Kerja Di Indonesia - Fadilla, Dini; Triani, Mike; Irfan, Muhammad (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
Indonesian natural resources have many opportunities. With 275 million people in Indonesia, 60% of whom are working-age, still not ready to increase labour productivity. This is all demonstrated by the relatively low percentage of labour productivity growth in Indonesia, which varies from province to province. The aim of this study is to provide an explanation and analysis of how education, health, and technology correlate with labour productivity in Indonesia.Panel data is used for analysis. During that period, Indonesia had 34 provinces.  After testing the model with the Chow and Hausman tests, the fixed-effect model is the best.  Research findings show that health does not affect labour productivity in Indonesia, but education and technology have a positive and significant impact on production.